Exploiting scents of distress: the prospect of manipulating herbivore-induced plant odours to enhance the control of agricultural pests - Turlings, Ted; Ton, Jurriaan (My University, 2006)
In response to feeding by arthropods, plants actively and systemically emit various volatile substances. It has been proposed that these herbivore-induced volatiles (HIPVs) can be exploited in agricultural pest control because they might repel herbivores and because they serve as attractants for the enemies of the herbivores. Indeed, recent studies with transgenic plants confirm that odour emissions can be manipulated in order to enhance the plants’ attractiveness to beneficial arthropods. An additional advantage of manipulating HIPV emissions could be their effects on neighbouring plants, as a rapidly increasing number of studies show that exposure to HIPVs primes plants for augmented defence expression. Targeting the right volatiles for enhanced emission should lead to ecologically and economically sound ways of combating important pests.